A New Formative Assessment for Indonesian Medical Records Education: Validating DOPSAT-RSP - Untoro Dwi Raharjo; Rizky Yuspita Sari; Resia Perwirani; Jannatul Iza Ahmad Kamal (Universitas Duta Bangsa Surakarta, 2026)
The assessment of practical skills among Associate Degree or Diploma 3 students of Medical Records and Health Information (MRHI) during field practice (PKL) lacks a standardized workplace-based assessment (WPBA) instrument, resulting in variations across institutions and potential subjectivity in evaluation. While Direct Observation of Procedural Skills (DOPS) is effective in clinical assessment but not fully suited to the non-clinical context of MRHI practice. This study aimed to modify DOPS into a formative assessment tool for MRHI field practice and to examine its validity and reliability. A research and development design was applied. The modified instrument, DOPSAT-RSP, underwent content validity testing by ten experts using the Content Validity Index (CVI) and Content Validity Ratio (CVR). Reliability testing included inter-rater reliability using Weighted Cohen’s Kappa and internal consistency using Cronbach’s alpha, involving two raters and 39 students. All items met content validity criteria (I-CVI ?0.900; CVR ?0.800; S-CVI =0.950). The Weighted Kappa value (0.774) indicated strong inter-rater agreement, while Cronbach’s alpha (0.952) demonstrated excellent internal consistency. The DOPSAT-RSP instrument is valid and reliable for formative assessment of D-3 RMIK students’ practical skills during PKL and shows potential for wider implementation with user training.